2002
DOI: 10.1183/09031936.02.00034402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of noninvasive ventilation on lung hyperinflation in stable hypercapnic COPD

Abstract: Effects of noninvasive ventilation on lung hyperinflation in stable hypercapnic COPD. O. Díaz, P. Bégin, B. Torrealba, E. Jover, C. Lisboa. #ERS Journals Ltd 2002. ABSTRACT: Two previous uncontrolled studies have suggested that noninvasive mechanical ventilation (NIMV) in patients with hypercapnic chronic obstructive pulmonary disease (COPD) improves arterial blood gas tensions by decreasing lung hyperinflation with the consequent reduction in inspiratory loads and changes in ventilatory pattern. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
1
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 80 publications
3
90
1
9
Order By: Relevance
“…Soares et al did not measure RV, FRC, and TLC. Our results also agree with those of Díaz et al, 8 who found that short-term noninvasive ventilation (bi-level positive airway pressure) significantly reduced RV (from 201 Ϯ 48% of predicted to 165 Ϯ 49% of predicted, P Ͻ .001) and TLC (from 173 Ϯ 36% of predicted to 148 Ϯ 35% of predicted, P Ͻ .001) in stable COPD patients. However, Díaz et al measured lung volumes with the nitrogen-washout method, the accuracy of which depends on all parts of the lung being well ventilated.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Soares et al did not measure RV, FRC, and TLC. Our results also agree with those of Díaz et al, 8 who found that short-term noninvasive ventilation (bi-level positive airway pressure) significantly reduced RV (from 201 Ϯ 48% of predicted to 165 Ϯ 49% of predicted, P Ͻ .001) and TLC (from 173 Ϯ 36% of predicted to 148 Ϯ 35% of predicted, P Ͻ .001) in stable COPD patients. However, Díaz et al measured lung volumes with the nitrogen-washout method, the accuracy of which depends on all parts of the lung being well ventilated.…”
Section: Discussionsupporting
confidence: 83%
“…Other studies of CPAP in stable COPD have yielded conflicting results; nevertheless, there is some evidence that CPAP prevents gas-exchange deterioration, improves quality of life, and reduces the need for hospitalization in patients with hypercapnia or nocturnal hypoventilation. 8,19,20 In addition to the favorable findings on CPAP for COPD exacerbation, some studies have found that CPAP either during or between exercise sessions can enhance the benefits of pulmonary rehabilitation. 1,2,21,22 However, the underlying mechanisms of CPAP benefits are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, NIV reduces total lung capacity by 10% in stable hypercapnic COPD, possibly from increased cross-sectional areas of the airways, decreased airway resistance, and increased expiratory time, which may facilitate the emptying of diseased lung units. 24,25 In contrast, other studies have shown that CPAP only temporarily decreases hyperinflation in COPD. 26 Similarly, high-resolution computed tomographic studies show that although low CPAP (5 cm H 2 O) may cause regional deflation in some subjects, higher CPAP (10 -15 cm H 2 O) may promote overinflation of already hyperinflated zones.…”
Section: Discussionmentioning
confidence: 62%
“…27 In our subjects with mustard airway disease, we found that NIV decreased functional residual capacity and residual volume non-significantly after 12 months.…”
Section: Discussionmentioning
confidence: 82%